Assessment of nutritional characteristics of products developed using soybean (Glycine max (L.) Merr.) pipeline and improved varieties - Alamu, Emmanuel Oladeji; Gondwe, T.N.P.; Phumzile, M.; Maziya-Dixon, B.B. (Informa UK Limited, 2017)
Breeding new varieties can introduce compositional differences in Soybean grains which could be caused by environment and climate factors, among other factors. Thus, there was need to evaluate these differences and also to investigate the applications of these varieties for product development at household level for improve nutrition. This study evaluated the nutritional, functional and pasting properties of pipeline and improved soybean varieties and of soy-based products. A total of six improved/pipeline soybean varieties and nine products were developed, which include six soy-fortified products using 80:20 wheat: soy flour blend and three soy-based products using 100% processed soybean grains, were milled and analysed. The moisture, fat and protein contents ranged from 4.91–6.13/100 g; 13.77–19.82/100 g and 31.78–36.56/100 g fresh weight, respectively. The lowest water absorption capacity (WAC) was observed for D.AL/Z 7 having 180.43% while D.AL/Z 8 had the highest value at 285.94%. Pasting viscosity ranged from 1.65–9.63 RVU. The results also showed that the ash, fiber and fat contents of Soy yoghurt are significantly (p < 0.05) lower compared with Soy tofu and Salad cream. Soy Tofu had a significant (p < 0.05) higher level of protein content (30.7/100 g FW).